2014
DOI: 10.1021/jp5037074
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposited Nanophotonics

Abstract: Prior work involving the detection and emission of light from semiconductor nanostructures has involved single crystalline nanomaterials. Here we review the use of electrodeposited, polycrystalline (pc), cadmium selenide (CdSe) in nanowires and nanogap device structures for photonics. The photodetectors and photon emitters we describe are symmetrical metal–semiconductor–metal (M-S-M) devices prepared either by the evaporation of two gold contacts onto linear arrays of pc-CdSe nanowires prepared using lithograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 149 publications
1
11
0
Order By: Relevance
“…This method may be of particular interest for interrogation of materials generated by low temperature, wet-chemical and maskless techniques. [48][49][50][51][52][53] In this work, Si was utilized for demonstration, but since the imaging relies only on the light absorption and charge separation abilities intrinsic to semiconductors, the method should be readily generalizable to a wide class of materials.…”
Section: Table Of Contents (Toc) Graphicmentioning
confidence: 99%
“…This method may be of particular interest for interrogation of materials generated by low temperature, wet-chemical and maskless techniques. [48][49][50][51][52][53] In this work, Si was utilized for demonstration, but since the imaging relies only on the light absorption and charge separation abilities intrinsic to semiconductors, the method should be readily generalizable to a wide class of materials.…”
Section: Table Of Contents (Toc) Graphicmentioning
confidence: 99%
“…The applicability of nanostructured materials is diverse and encompasses electrocatalysis, photocatalysis and heterogeneous catalysis as well as surface enhanced Raman spectroscopy, nanophotonics, energy storage, additive manufacturing and electrochemical based sensing for a variety of important biological and inorganic analytes ,,. As an example of the latter, the detection of nitrite has received significant attention .…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of nanostructured materials is diverse and encompasses electrocatalysis, photocatalysis and heterogeneous catalysis as well as surface enhanced Raman spectroscopy, nanophotonics, energy storage, additive manufacturing and electrochemical based sensing for a variety of important biological and inorganic analytes. [4,[9][10][23][24][25][26][27][28][29][30][31] As an example of the latter, the detection of nitrite has received significant attention. [32][33][34][35] Nitrite is an essential component of a healthy diet as it reacts with hemoglobin and produces methemoglobin which enables transporting of oxygen at the cellular level.…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical formation of nanostructured materials is a relatively mature field, however, there are consistently new methods and strategies being reported that allow excellent control over composition, size, shape and exposed crystal facets [1][2][3][4][5][6][7]. This is particularly useful given the critical role the aforementioned properties play in electrocatalysis, photocatalysis, surface enhanced Raman spectroscopy and electroanalytical chemistry.…”
Section: Introductionmentioning
confidence: 99%